Desain Interaksi Telepon Genggam Untuk Anak-Anak Dengan Fitur Pemantau GPS Melalui SMS Berbasis Arduino Nano - Ivana Agustina; Hurriyatul Fitriyah; Mochammad Hannats Hanafi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Handphone is a portable telecommunication device. Currently, mobile phones are available in many kinds with many features and applications. As a result, children often use it out of bounds and have negative impact. Security is important for everyone, as well as children, especially the underage. Child abduction cases are concern for parents. Therefore, ensuring children's safety in their environment such as in school is very important. Efforts that parents can do is communication to monitor their children. Global Positioning System (GPS) is tool to provide information about existence of its users. To facilitate the communication of children with parents, this research will be made a mobile phone for children with principle of interaction design.. This mobile phone has LCD screen as call viewer and 4 push button. Push buttons have emoticon to calls to father, mother, teacher, and receive incoming call. From the test results, the functionality of mobile phone has been able to function according to input from the user. In the performance of the tool, obtained an average of 2.4 seconds for each user to press the push button. On usability, involving 20 students of Children Centre Brawijaya Smart School. In the questionnaire test of the usefulness, easy to use, ease to learn, and satisfaction, obtained an average value of 1 which means yes, from the likert scale 1 to 3.